PhosphoFlowSeq – A High-throughput Kinase Activity Assay for Screening Drug Resistance Mutations in EGFR. Issue 22 (5th November 2021) - Wagner, Anja; Teufl, Magdalena; Gold, Lukas; Lehner, Manfred; Obinger, Christian; Sykacek, Peter; Traxlmayr, Michael W.
Graphical abstract: Abstract: Drug resistance poses a major challenge for targeted cancer therapy. To be able to functionally screen large randomly mutated target gene libraries for drug resistance mutations, we developed a biochemically defined high-throughput assay termed PhosphoFlowSeq. Instead of selecting for proliferation or resistance to apoptosis, PhosphoFlowSeq directly analyzes the enzymatic activities of randomly mutated kinases, thereby reducing the dependency on the signaling network in the host cell. Moreover, simultaneous analysis of expression levels enables compensation for expression-based biases on a single cell level. Using EGFR and its kinase inhibitor erlotinib as a model system, we demonstrate that the clinically most relevant resistance mutation T790M is reproducibly detected at high frequencies after four independent PhosphoFlowSeq selection experiments. Moreover, upon decreasing the selection pressure, also mutations which only confer weak resistance were identified, including T854A and L792H. We expect that PhosphoFlowSeq will be a valuable tool for the prediction and functional screening of drug resistance mutations in kinases.